Thermally conductive and electrically insulating EVA composite encapsulant for solar photovoltaic (PV) cell (eXPRESS Polymer Letters, 2008)
A new way of improving the heat dissipating ability and PV efficiency of the solar cells by enhancing the thermal conductivity of the rear EVA layer was reported. The thermal conductivity, electrical resistivity, degree of curing of the EVA encapsulating composites and the PV efficiency of the solar cells are investigated. Filling with the thermal conductive fillers enhances the thermal conductivity of the composites effectively. The thermal conductivity of the filler influences significantly the thermal conductivity of the composite at high filler loading (greater than 20 vol%). Thermal conductivities of the composites filled with SiC, ZnO or BN reach respectively 2.85, 2.26 and 2.08 W/m•K at filler content of 60 vol%. The composites filled with ZnO or BN exhibit superior electrical insulation to those filled with SiC or Al2O3. ZnO can promote the cross-linking reaction of the EVA matrix. The test results indicated that the EVA composite encapsulating rear films filled with thermal conductive fillers are able to improve the PV efficiency and the heat dissipating ability of the solar cell effectively.